Quorum sensing inhibition as a promising method to control biofilm growth in metalworking fluids. (1st August 2019) - Özcan, Safiye Selen; Dieser, Markus; Parker, Albert E; Balasubramanian, Narayanaganesh; Foreman, Christine M
Abstract: Microbial contamination in metalworking systems is a critical problem. This study determined the microbial communities in metalworking fluids (MWFs) from two machining shops and investigated the effect of quorum sensing inhibition (QSI) on biofilm growth. In both operations, biofilm-associated and planktonic microbial communities were dominated by Pseudomonadales (60.2–99.7%). Rapid recolonization was observed even after dumping spent MWFs and meticulous cleaning. Using Pseudomonas aeruginosa PAO1 as a model biofilm organism, patulin (40 µM) and furanone C-30 (75 µM) were identified as effective QSI agents. Both agents had a substantially higher efficacy compared to α-amylase (extracellular polymeric substance degrading enzyme) and reduced biofilm formation by 63% and 76%, respectively, in MWF when compared to untreated controls. Reduced production of putatively identified homoserine lactones and quinoline in MWF treated with QS inhibitors support the effect of QSI on biofilm formation. The results highlight the effectiveness of QSI as a potential strategy to eradicate biofilms in MWFs.